Experience with Vacuum-Assisted Closure in the Management of Postpneumonectomy Empyema: An Analysis of Eight Cases - Karapinar, Kemal; Saydam, Özkan; Metin, Muzaffer; Erdogan, Sertan; Aker, Cemal; Arik, Burcu; Citak, Necati (The Thoracic and Cardiovascular Surgeon, 2016)
Background The treatment of postpneumonectomic empyema is challenging. The aim of this study was to test the efficacy of vacuum-assisted closure (VAC) in the treatment of patients with open window thoracostomy (OWT).Methods Between January 2010 and April 2014, eight patients developed empyema following pneumonectomy for malignant diseases in our department and then underwent an OWT with subsequent VAC therapy; their cases were retrospectively studied. Each session of VAC therapy lasted 72 hours, and therapy was completed after approximately 6 sessions.Results OWT in six patients resulted in either decreased size or complete closure after VAC treatment. Five patients had a bronchopleural fistula (BPF), which was closed either with a tracheal stent (three patients), primary suture, or omentoplasty. The BPF in one of these patients closed during VAC therapy. The treatment failed in two patients due to the microfistula becoming obvious in one and persistence of the fistula in the other.Conclusion We believe that the use of VAC in the treatment of postpneumonectomy empyema is effective, except for patients with BPF.
Keywords: vacuum-assisted closure; empyema; pneumonectomy